An Appropriate Diagnosis of Dengue Virus Infection in Some Cases who had and were being Treated in Soerya Hospital Sepanjang â Indonesia - Soegijanto, Soegeng; Wikanesthi, Desiana; Chilvia, Eva; Soedirham, Oedojo (Institute of Topical Disease, 2015)
Since January 2014, Soerya Hospital has found many cases with positive result of NSÂ or IgM and IgG Dengue. The clinical manifestations mostly were high fever with headache, vomiting and also malaise convulsion and unconsciousness. Aim of the study is to find out an appropriate diagnosis of Dengue Virus Infection. Observasional study had been done since JanuaryâApril 2014 with 50 cases of dengue Virus Infection. The diagnostic procedure was made based on the WHO 2011 criteria. Result Many cases had come with fever within couple days, some of them showed convulsions. Therefore, it should be made a differential diagnosis with other disease, such as acute tonsilopharingitis, etc. The patient also had to be tested with NS1Â if the patient come in the first, second and third day of fever and followed by IgM/IgG dengue on the fourth, fifth or sixth days of fever. The diagnosis of Dengue Virus Infection was made based on the WHO criteria 2011.Â This study showed that not all cases showed positive result of NS1Â or IgM/IgG dengue on the first or second test. For the negative result, we should not think that the case is not a case of Dengue Virus Infection, especially if it happens at Aedes aegypti breeding season, the patient should be observed and performed the test again to get a proper diagnosis for Dengue Virus Infection. Monitoring clinical manifestation should always be done, to predict the appropriate diagnosis of Dengue Virus Infection.